Diagnosis determination of chronic periapical abscess case using imaging radiography software and microbiological examination in female patients - Prisinda, Diani; Malinda, Yuti; Lita, Yurika Ambar; Tjahajawati, Sri (Universitas Padjadjaran, 2019)
Introduction: Diagnosis determination of chronic periapical abscess can be achieved by subjective, objective, and other examination such as radiographic and microbiological examination based on clinical finding and differences intensity at the periapical area with healthy bone suspected to be chronic abscess periapical. A microbiological examination performed to obtain the predominant bacteria that involved to determine an adequate medicament to succeed endodontic treatment. This study was aimed to compare intensity abscess lesion segmentation image reconstruction and surrounding bone for determine the diagnosis of periapical abscess more accurately and to determine the characteristic of bacteria colony from a periapical abscess tooth. Methods: The study sampling method was consecutive sampling (6 female) consisted of inclusion criteria patient with a periapical lesion in anterior maxillary that diagnosed based on clinical signs and symptoms. CBCT 3D scan of the maxillofacial region taken from of patients was measured image intensity periapical lesion and surrounding bone using semi-auto segmentation with ITK-SNAP 3.6.0. Samples from the root canals taken using three sequential sterile paper points. The samples were plated, and microorganisms were then isolated and identiﬁed by the colony characteristics. Results: There was a signiﬁcant difference between the mean content of lesion intensity of (n = 6,256.710 ± 81.930 and 636.022 ± 79.981 lesion boundary. The two-tailed p-value = 0.0050, this difference was considered to be very statistically significant. The mean of group lesion minus group surrounding bone equals to 163.715. 95% confidence interval of this difference from 75.542 to 251.888. Conclusions: Demineralisation of periapical bone can be determined by voxel intensity value in CBCT 3D radiograph using semi-auto segmentation ITK SNAP, could be recommended as a quantitative interpretation for detection periapical lesion and chronic periapical abscesses is a poly-microbial disease. Keywords: Chronic periapical abscess, endodontic, microbiology, radiograph CBCT